2020
DOI: 10.1021/acssensors.0c00117
|View full text |Cite
|
Sign up to set email alerts
|

Naked-Eye Detection of Ethylene Using Thiol-Functionalized Polydiacetylene-Based Flexible Sensors

Abstract: Ethylene is a hormone that plays a critical role in many phases of plant growth and fruit ripening. Currently, detection of ethylene heavily relies on sophisticated and timeconsuming conventional assays such as chromatography, spectroscopy, and electrochemical methods. Herein, we develop a polydiacetylene-based sensor for the detection of ethylene via color change. The sensors are prepared through the reaction between polydiacetylene and Lawesson's reagent that results in decorating polydiacetylene with termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 57 publications
(99 reference statements)
1
52
0
1
Order By: Relevance
“…As shown in Figure S10, Supporting Information, we performed the mapping using the excitation laser of 785 nm over a 180 µm × 180 µm area and obtained the RSD of 3.3% for the BPE sample, better than the R6G sample (i.e., 4.4%), validating the prediction of the chemical binding. On the other hand, it has been reported that introducing thiol groups to existing molecules or using thiol molecules as a bridge to connect molecules with sensing chips [ 82–84 ] can improve the sensing performance of non‐thiol‐based molecules. These emerging strategies are promising to expand the impact of the proposed nanogap sensing architectures.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S10, Supporting Information, we performed the mapping using the excitation laser of 785 nm over a 180 µm × 180 µm area and obtained the RSD of 3.3% for the BPE sample, better than the R6G sample (i.e., 4.4%), validating the prediction of the chemical binding. On the other hand, it has been reported that introducing thiol groups to existing molecules or using thiol molecules as a bridge to connect molecules with sensing chips [ 82–84 ] can improve the sensing performance of non‐thiol‐based molecules. These emerging strategies are promising to expand the impact of the proposed nanogap sensing architectures.…”
Section: Resultsmentioning
confidence: 99%
“…Drawing inspiration from biological olfactory systems, many food sensors have been designed for inclusion into packaging and processing to indicate food quality by monitoring gas composition. Common markers for gas‐targeting food sensors include carbon dioxide, [ 31,43 ] oxygen, [ 44–48 ] volatile organic compounds (VOCs), [ 49–52 ] and biogenic amines (BAs). [ 21,53–56 ]…”
Section: Food Sensorsmentioning
confidence: 99%
“…Recently, we presented an adaption of our meat sensing technology to monitor fruit ripening. [ 51 ] PDA vesicles were functionalized to detect ethylene (LOD = 600 ppm) by substituting the carboxylic acid head group of PDA with a thiol functional group. Ethylene reacts with the thiol head group of the PDA and forms thiolene, which changes the degree of conjugation in the PDA membrane and results in a blue to red color change.…”
Section: Challenges and Opportunities In Food Sensorsmentioning
confidence: 99%
“…Ethylene sensors based on chemoresistive [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], optical (NDIR) [19][20][21][22], colorimetric [23][24][25], luminescence [26], fluorescence [27], piezoelectric [28][29][30], and electrochemical [31][32][33][34] principles have been developed. Each such principle has its own advantages and limitations, the comparison of which can be found in several review articles [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%